2020
DOI: 10.1097/ede.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Relationships Between Proactive Reporting State-level Prescription Drug Monitoring Programs and County-level Fatal Prescription Opioid Overdoses

Abstract: Background: Prescription drug monitoring programs (PDMPs) that collect and distribute information on dispensed controlled substances have been adopted by nearly all US states. We know little about program characteristics that modify PDMP impact on prescription opioid overdose deaths. Methods:We measured associations between adoption of any PDMP and changes in fatal prescription opioid overdoses in 2002-2016 across 3,109 counties in 49 states. We then measured changes related to the adoption of "proactive PDMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Harm reduction efforts such as expansion of naloxone access, as well as efforts to regulate opioid prescribing through prescription drug monitoring programs and pain management clinic laws, have been associated with reductions in opioid overdose deaths (107)(108)(109)(110)(111)(112). Indeed, following investment in multiple efforts to curb high risk prescribing and regulate overall opioid prescribing, prescription opioid overdose rates leveled off (although they did not decrease).…”
Section: Implications For Actionmentioning
confidence: 99%
“…Harm reduction efforts such as expansion of naloxone access, as well as efforts to regulate opioid prescribing through prescription drug monitoring programs and pain management clinic laws, have been associated with reductions in opioid overdose deaths (107)(108)(109)(110)(111)(112). Indeed, following investment in multiple efforts to curb high risk prescribing and regulate overall opioid prescribing, prescription opioid overdose rates leveled off (although they did not decrease).…”
Section: Implications For Actionmentioning
confidence: 99%
“…State governments have enacted an array of policy strategies to address the opioid epidemic. For instance, the creation of Prescription Drug Monitoring Program's (PDMPs), state-run electronic databases that allow prescribers, dispensers, and other health authorities to track the prescription patterns of controlled substances for individual patients, has become a widely adopted policy intervention used by states to reduce the amount of opioid painkillers prescribed to patients ( Bao et al, 2017 ; Cerdá et al, 2020 ; Fink et al, 2018 ). States have also enacted other policy interventions such as laws that aim to regulate pain management clinics, increase access to naloxone, and improve legal protections for bystanders who report drug overdoses as they are occurring.…”
Section: Introductionmentioning
confidence: 99%
“…92,93 Six studies found that mandatory use of PDMPs, including unsolicited and proactive reporting of patient prescription histories, improved opioid-related outcomes. [94][95][96][97][98][99] ThesepositivefindingsonstrongPDMPswere notuniform:1studyfoundnosignificantassociationbetween mandatory use requirements and the number of opioid prescriptions among patients undergoing general surgical procedures 100 and another study found that strong and weak PDMPs were associated with similar changes in opioid prescription rates, the number of cumulative doses, and prescriptionlength(indays)amongMedicarebeneficiaries. 101 Studies published after our review period investigated GoodSamaritanlaws,painclinicandmarijuanaregulations, prescribing guidelines, and educational interventions.…”
Section: Discussionmentioning
confidence: 94%